University Desertion and Retention: A Bibliographical Study - Fernández Hileman, María Del Rosario; Corengia, Ángela; Durand, Julio (Pensando Psicología, 2014)
This article presents a bibliographical study of the phenomena of university desertion and retention, including a review and summary of the main empirical studies and theoretical perspectives that addressthis subject in Argentina and other countries. Firstly, the problem of desertion is shown in numbers, in specific terms and in Argentinian and international contexts. Next, the article looks at substantive conceptual perspectives based on sociological, psychological, organizational, economic and cultural theories, as well as the empirical studies that support these along with other theoretical clarifications. Within the framework of these empirical studies, the study then highlights actions and programs carried out over the past 40 years to improve retention in higher education. Finally, conclusions are offered as material for future research.